The Impact of Routine and Non-Routine CEO Turnover on Earnings Management - Vernando, Andreas; Ainy, Rintan Nuzul; Sumaryanto, (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aims at examining the practice of earnings management by focusing on the routine and the non-routine CEO turnover.Design/methodology/approach: The sample in the study consists of all non-financial companies that are listed in the Indonesia stock exchange from 2004 to 2014. We utilize the multiple regression analysis both to test the hypothesis and additional analysis.Findings: The findings reveal that the successor CEO will aggressively manage earnings during the non-routine turnover, while we do not find that the predecessor CEO engage in earnings management during the routine turnover.Research limitations/implications: We classify the routine and the non-routine CEO turnover by browsing relevant articles and the official newspaper from the Internet. If we cannot identify, we follow the methods of Kang and Shivdasani (1995) who classify that routine turnover is when the predecessor CEOs still serve the board of commissioners and non-routine turnover is when the predecessor CEOs do not serve the board of commissioners.Practical implications: The results of this study provide insight for investors and boards of commissioners in order to assess the performance of the CEO in the first year of their service.Originality/value: This research provides evidence on the importance to differ the routine and non-routine CEO turnover because they have a distinct effect in earnings management.